Розробка процесу імпульсного електроплазмолізу бурякової сировини та удосконалення способу її теплової обробки - Серебряков, Роман Анатолійович (My University, 2002)
Дисертацію присвячено експериментальним та модельним дослідженням з розробки процесу імпульсного електроплазмолізу та використання його в поєднанні з попередньою тепловою обробкою. Встановлено, що ефективність електроплазмолізу тканини цукрового буряку залежить як від напруженості електричного поля, так і від тривалості імпульсів та міжімпульсних пауз імпульсного електричного поля. Simultaneous pulsed electroplasmolysis and heat treatment of sugar beet has been investigated. Electroplasmolysis efficiency can be influenced by electric field strength and pulse width and pulse frequency. Electrical treatment time no more than characteristic time of moisture migration in the tissue has been recommended (about 1 s for sugar beet tissue). It was concluded that the optimal conditions of combined treatment require pulsed electric field plasmolysis of beetroot stuff heated up to about 50-55°С in order to minimize the energy consumption. The main results of the present study have been successfully valorized at two sugar plants.
Keywords: імпульсне електричне поле; електроплазмоліз; комбінована обробка; цукровий буряк; pulsed electric field; electroplasmolysis; combined treatment; sugar beet